MACHADO DE ASSIS E A LITERATURA BRASILEIRA DO OITOCENTOS: UM PROJETO DE LITERATURA NACIONAL (Revista de História Regional, 2007)
Our aim, in this work, were to reach a different vision about ideologics attitudes of Machado de Assis when in beginning of your literary career, as articulist, and your opinions about the national literature. We intend to demonstrate how, even in Machado, there is the manifestation of one civilizing preoccupation that give the tonus of our literature during all Brazilian nineteenth century. Toreach this aim, we utilize one only article, in which are more evidents the symptoms of this attitude of esthetizing and moralizing character.